2017
DOI: 10.1002/acp.3340
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Credibility for a Memory Report of a Single Versus Repeated Event

Abstract: When a person experiences an event that has multiple similar instances (i.e., a repeated event), memories for details that change across instances can be challenging to recall (e.g., Fivush, 1984). We expected that third parties would perceive memory reports of instances of repeated events as less credible than unique (i.e., single) events.Undergraduates participated in a single or repeated event, during which critical details were presented. Participants were asked to recall the session 2-days later, and memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 55 publications
2
30
4
Order By: Relevance
“…To date, two experiments have directly investigated the perceptions of individuals recalling a repeated event. These experiments used a two‐phase methodology wherein adult evaluators assessed the credibility of child (Connolly, Price, Lavoie, & Gordon, 2008) and adult speakers (Weinsheimer, Coburn, MacLean, & Connolly, 2017). In the first phase of these experiments, phase 1 participants experienced a single event (a play session and tasting session respectively) or a repeated event in which most details varied predictably across episodes.…”
Section: Perceptions Of Repeated‐event Speakersmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, two experiments have directly investigated the perceptions of individuals recalling a repeated event. These experiments used a two‐phase methodology wherein adult evaluators assessed the credibility of child (Connolly, Price, Lavoie, & Gordon, 2008) and adult speakers (Weinsheimer, Coburn, MacLean, & Connolly, 2017). In the first phase of these experiments, phase 1 participants experienced a single event (a play session and tasting session respectively) or a repeated event in which most details varied predictably across episodes.…”
Section: Perceptions Of Repeated‐event Speakersmentioning
confidence: 99%
“…In both studies evaluators received no contextual information indicating that the speaker may be lying. Weinsheimer et al (2017) informed participants that the speaker was recalling an event which they had previously experienced. Connolly et al (2008) also told evaluators that the speaker was recalling a past event, and that some speakers were highly accurate in recall whilst the accuracy of others was low.…”
Section: Perceptions Of Repeated‐event Speakersmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, this research focused on cued recall responses to direct questions; however, this is not best practice interviewing. Research employing a best practice questioning methodology showed that adult witnesses who experienced repeated events were less accurate than single‐event witnesses (Theunissen et al, ) and may appear less reliable (Weinsheimer, Coburn, Chong, MacLean, & Connolly, ). Pursuing research that reveals how features like deviations or PEI influence witness reporting in a best practice interview scenario is important.…”
Section: Limitationsmentioning
confidence: 99%